Enhanced Removal of Lead by Chemically and Biologically Treated Carbonaceous Materials - Mohamed E. Mahmoud; Maher M. Osman; Somia B. Ahmed; Tarek M. Abdel-Fattah (The Scientific World Journal)
Hybrid sorbents and biosorbents were synthesized via chemical and biological treatment of active carbon by simple and direct redox reaction followed by surface loading of baker’s yeast. Surface functionality and morphology of chemically and biologically modified sorbents and biosorbents were studied by Fourier Transform Infrared analysis and scanning electron microscope imaging. Hybrid carbonaceous sorbents and biosorbents were characterized by excellent efficiency and superiority toward lead(II) sorption compared to blank active carbon providing a maximum sorption capacity of lead(II) ion as 500 μmol g−1. Sorption processes of lead(II) by these hybrid materials were investigated under the influence of several controlling parameters such as pH, contact time, mass of sorbent and biosorbent, lead(II) concentration, and foreign ions. Lead(II) sorption mechanisms were found to obey the Langmuir and BET isotherm models. The potential applications of chemically and biologically modified-active carbonaceous materials for removal and extraction of lead from real water matrices were also studied via a double-stage microcolumn technique. The results of this study were found to denote to superior recovery values of lead (95.0–99.0±3.0–5.0%) by various carbonaceous-modified-bakers yeast biosorbents.